Contrasting monetary and multidimensional poverty in India: a spatial perspective - Soumyabrata Mondal; Saheli Kumar; Anand Prasad Mishra (Belgeo)
The present study makes a comparative analysis on the spatial pattern of poverty by considering both monetary and multidimensional approach and assesses the variation or gap in poverty estimation. Two latest available datasets i.e. NSSO data of planning commission report regarding monetary or consumption poverty and the baseline report on multidimensional poverty by NITI Aayog have been used. Our analysis shows that significant interstate disparities are observed in the spatial concentration of poverty applying two different approaches. Extreme monetary poverty persist in states like Chhattisgarh (39.9 percent), Karnataka (37.0 percent), Meghalaya (36.9 percent) etc. whereas extreme multidimensional poverty exists in Bihar (51.9 percent) followed by Jharkhand (42.2 percent). The result reveals the fact that though monetary poverty and multidimensional poverty are associated with each other the strength of relationship between these two approaches is not strong enough. The study strongly recommends the incorporation of the multidimensional approach along with the consumption approach to measure poverty which has high policy relevance.